2018
DOI: 10.1021/acschemneuro.8b00086
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipid Headgroups Control Rate and Mechanism of Superoxide Dismutase-1 Aggregation and Accelerate Fibrillization of Slowly Aggregating Amyotrophic Lateral Sclerosis Mutants

Abstract: Interactions between superoxide dismutase-1 (SOD1) and lipid membranes might be directly involved in the toxicity and intercellular propagation of aggregated SOD1 in amyotrophic lateral sclerosis (ALS), but the chemical details of lipid-SOD1 interactions and their effects on SOD1 aggregation remain unclear. This paper determined the rate and mechanism of nucleation of fibrillar apo-SOD1 catalyzed by liposomal surfaces with identical hydrophobic chains (RCH(OCH)), but headgroups of different net charge and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Previous studies have shown that the stochastic fibrillization of SOD1 not only manifests in variation in observed lag time and propagation rate but also in the maximal ThT fluorescence reached during an iterate assay. , In this study, and previous studies, , the maximum ThT fluorescence of iterate assays of unseeded WT fibrillization varied 10-fold from well to well, typically ranging from 40 to 400 A.U. (Figures B, , and ).…”
Section: Results and Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have shown that the stochastic fibrillization of SOD1 not only manifests in variation in observed lag time and propagation rate but also in the maximal ThT fluorescence reached during an iterate assay. , In this study, and previous studies, , the maximum ThT fluorescence of iterate assays of unseeded WT fibrillization varied 10-fold from well to well, typically ranging from 40 to 400 A.U. (Figures B, , and ).…”
Section: Results and Discussionsupporting
confidence: 70%
“…Approximately 2% of cases of amyotrophic lateral sclerosis (ALS) are caused by >160 different mutations in the gene encoding Cu, Zn superoxide dismutase (SOD1), a homodimeric enzyme. Most mutations have an autosomal dominant mode of inheritance, resulting in heterozygous individuals. The self-assembly of mutant and wild-type (WT) forms of SOD1 into amyloid-like oligomers is hypothesized to trigger ALS pathogenesis via a prion-like mechanism. Measuring the rate of self-assembly of WT and ALS mutant SOD1 into amyloid-like speciesand doing so reliably and reproduciblyis important for: (i) understanding whether mutations induce toxicity by altering intrinsic rates of self-assembly , or interactions with other proteins or membrane surfaces and (ii) discovering agents that inhibit or detoxify SOD1 aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…When incubated with phospholipids, Rasouli et al . (2018) found SOD1 aggregation was influenced by the charge of the head group, lipid concentration and the SOD1 variant. For example, anionic phospholipids greatly stimulated metal-free wild-type SOD1 fibril formation over a broad range of concentrations whereas zwitterionic did not.…”
Section: Sod1 Aggregation In Alsmentioning
confidence: 99%
“…The ability of S-XL6 to diminish aggregates is expected based upon S-XL6-mediated stabilization of SOD1 variants, given that stabilization increases the time required for the nucleation phase of aggregation. We are currently unable to measure the rates of aggregation because existing assays require reductants that would also remove S-XL6 [38,39]. peptide (purple) linked by S-XL6.…”
Section: Structural Analysis Of S-xl6 Cross-linked Fals Sod1 Variantsmentioning
confidence: 99%